G45 Haematocolpos due to a transverse vaginal septum in 15 year old girl with junctional epidermolysis bullosa. (7th April 2014) - Solman, L; Mellerio, JE; Mustaq, I; Martinez, AE
Abstract : Our female patient presented as a neonate with extensive skin loss and fragility. Herlitz junctional epidermolysis bullosa (JEB) was diagnosed on the basis of complete absence of skin immunoreactivity to laminin 332 and she was found to be homozygous for a recurrent hotspot mutation in the LAMB3 gene, R635X. Two elder brothers with the same diagnosis had died previously. On routine clinic review at age 15 years, she complained of two months of intermittent lower abdominal pain. Examination of her abdomen revealed a large, mildly tender mass arising from the pelvis. She had Tanner stage 4 normal external genitalia with an intact hymen and normal breast development. She had not started menstruating. A pregnancy test was negative. Abdominal and pelvic ultrasound demonstrated a large haematocolpos, measuring 10.2 × 9.5 x 16.9 cm (858 ml) in size. Magnetic resonance imaging of confirmed the haematocolpos, with small amount of blood within the endometrial cavity but no haematosalpinx. A low vaginal obstruction was present near the introitus. The patient underwent successful division of the transverse vaginal septum under general anaesthetic, which was uneventful despite a known EB-related posterior glottic web obstructing 60% of her airway. She healed well post-operatively without vaginal scar formation and has subsequently had regular periods. This is the first case report of haematocolpos in Herlitz JEB. It is highly unusual for patients with this type of EB to survive to adolescence as they usually succumb to life-threatening airway obstruction, sepsis or profound failure to thrive in the first few years of life. As in other chronic inflammatory diseases pubertal delay is commonly seen in adolescents with severe types of EB and the aetiology is multifactorial. In contrast, our patient had reached puberty, however, a vaginal septum, presumed secondary to her inherent mucocutaneous fragility, had prevented menstruation. Monitoring to assess pubertal status is important in this group of complex patients, with awareness that there may be delay and a need for medical and psychological input.